Early Complications after Isolated Coronary Artery Bypass Grafting: Predictors and Perioperative Pharmacological Therapy - Shklianka, I. V.; Zharinov, O. J.; MikhalievК. O.; Yepanchintseva, O. A.; Todurov, B. M. (Ukrainian Journal of Cardiovascular Surgery, 2019)
Cardiac surgery is associated with the development of early postoperative complications (EPC) such as postoperative arrhythmias, neurological disorders, renal and pulmonary insufficiency, secondary platelet dysfunction, systemic inflammation response, etc. The aim. To determine predictors of early postoperative complications in patients after isolated CABG. Materials and methods. In a single-center study, data from clinical and instrumental examination of 155 patients with stable coronary heart disease (CHD), successively selected for an isolated coronary artery bypass surgery (CABG), were analyzed. In 66 patients, 84 early postoperative complications were reported during the hospital period, 89 patients had no complications. Groups of patients with and without complications were compared in terms of demographic indicators, comorbidities, echocardiographic and laboratory parameters, perioperative therapy, and features of CABG surgery. Results. Most of the early complications (56 %) were the cases of postoperative atrial fibrillation. A unifactor analysis showed that the patients with complications in the early postoperative period typically had severe diabetes (p = 0.025), I and II degree of obesity (p = 0.070), LV hypertrophy (p = 0.008), enlarged left atrium (p = 0.068); elevated preoperative level of IL-6 (p = 0.044); absence of statin therapy in perioperative period (p < 0.001) and prolonged duration of aortic clamping (p = 0.049). According to the multivariate analysis, the risk of EPC after CABG was 2.5 times higher in patients who did not take statins in the perioperative period, compared to those who received high doses of statins for ≥ 7 days or low/ moderate doses of statins. In patients with severe diabetes, the risk of EPC was 1.96 times higher than that in patients with mild diabetes. Conclusions. High-dose statin therapy for ≥ 7 days prior to surgery allowed to reduce the risk of early complications, particularly, postoperative atrial fibrillation.